Historiography of Pesantren in Indonesia: Challenges and Opportunities: Historiografi Pesantren di Indonesia: Tantangan dan Peluang - Mutawally, Anwar Firdaus (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Studi Islam Sunan Doe, 2023)
This study aims to determine the development of pesantren historiography, themes, and problems in Indonesia. The method used in this study is the historical method and research techniques using library research. The study results show that the historiography of Islamic boarding schools in Indonesia has undergone three periods, namely traditional, colonial and modern historiography. The themes studied in pesantren historiography include biography, intellectual history, and socio-religious history. The problems that occur in the historiography of pesantren include the lack of effort by historians to publish their works. The solution offered is to add environmental history to enrich the historiography of the pesantren.